IDENTIFICATION OF PROBLEMS IN ADULT AGE WITH THE RISK OF STROKE IN JATIMELATI VILLAGE - ACHIRDA, NUR; SATIVANI, ZAHRA (IFI cabang Kota Bekasi, 2024)
Physical activity is very important for people both young and old. Lack of physical activity can cause several health risks that can interfere with daily life. One of them is hypertension. Stroke can be caused by high or uncontrolled blood pressure. This community service aims to identify health problems in adults with a risk of stroke in the Jatimelati sub-district. This community service activity was carried out on April 20 2024 with a total of 30 participants. This activity is carried out by identifying health problems and following up. Identify health problems that arise, including diabetes mellitus, hypertension and cholesterol. The activity continues with evaluation through counseling or education and exercise. The exercise carried out is low impact aerobic exercise. Keywords: physical activity, hypertension, stroke, low impact aerobic exercise